Sexually Transmitted Infection Prevention With Long-Acting Reversible Contraception: Factors Associated With Dual Use. Issue 7 (July 2017) - Thompson, Erika L.; Vamos, Cheryl A.; Griner, Stacey B.; Logan, Rachel; Vázquez-Otero, Coralia; Daley, Ellen M.
Abstract : Background: Long-acting reversible contraception (LARC) is extremely effective in preventing pregnancy; however, it does not provide sexually transmitted infection (STI) prevention. Therefore, dual use is recommended for the prevention of STIs, in addition to pregnancy, by using LARC methods with condoms. This study assessed factors associated with LARC only use and dual-LARC and condom use among college women. Methods: The National College Health Assessment-II Fall 2012 to 2013 was used for this analysis. The analytic sample was restricted to women who used a LARC method (ie, intrauterine device or implant) (N = 1658). The main outcome was dual method use, LARC and condom, at last sex. An adjusted logistic regression model assessed sociodemographic factors (age, relationship, race), health care utilization (routine gynecological examination), and sexual behavior (number of partners) as factors associated with dual condom-LARC use at the last time of vaginal-sex. Prevalence ratios (PR) and 95% confidence intervals (CI) were estimated. Results: Among women reporting LARC use, 24% used a condom. Dual users were less likely to have only 1 sexual partner (adjusted PR [aPR], 0.66; 95% CI, 0.54–0.81) and be in a relationship. Dual users were more likely than LARC-only users to be Hispanic (aPR, 1.34; 95% CI, 1.01–1.78), black (aPR, 1.40; 95% CI, 1.07–1.83), and biracial/multiracial (aPR, 1.38; 95% CI, 1.10–1.73). Conclusions: These findings illustrate differences between dual-condom LARC and LARC-only college users. It is likely that relationship status and number of partners influences perceived risk for STIs and decision making for dual use among this population. Abstract : Condom use among long-acting reversible contraception users is less common among women with fewer sexual partners and in relationships.